“Bringing individual experience back into social theory: Beyond Luhmann, with the help of Hannah Arendt, Gunther Teubner and Jan Philipp Reemtsma” - Guibentif, P. (“Niklas Luhmann 20 Years After. Constructing Law in World Society”, 2018)
The purpose of the paper is to outline a theoretical proposal that brings individual experience back into social theory. This proposal is mainly based on Niklas Luhmann's systems theory, taking into account inputs from Hannah Arendt, Gunther Teubner and Jan Philipp Reemtsma.